Combined effects of irrigation management and nitrogen fertilization on soft wheat productive responses under Mediterranean conditions - Oliveira, Patrícia (2019)
To evaluate water-nitrogen interactions on irrigated wheat production, it is important to know: The dose, the fractioning, and the most recommended period of fertilizers application; the best irrigation volumes and schedules for meeting the crop requirements, ensuring the minimum leaching risks, to obtain the highest yields and quality of the grain, while achieving high water and nitrogen use efficiencies. This study evaluated the interactive effect of irrigation and nitrogen fertilization, with conventional and enhanced efficiency fertilizers, on yield, irrigation water use efficiency and grain quality of soft wheat. For this purpose, two trials were carried out during the 2016/2017 in Beja, Alentejo, under two irrigation strategies: D1 (100% of crop evapotranspiration-ETc-throughout the cycle) and D2 (100% of ETc only at four stages: Beginning of stem extension; booting; heading; grain filling). In one trial, enhanced efficiency N fertilizers were applied through 6 splitting treatments. In the other, conventional N fertilizer was applied through 5 splitting treatments. The results suggest that, on one hand, early applications of advanced efficiency fertilizers do not compromise the crop yield and, on the other hand, the availability of nitrogen in the booting stage is important to obtain higher grain protein content.